Spatiotemporal variation of crop diversification across Eastern Indo Gangetic plains of South Asia - Ravi Nandi; Arunava Ghosh; Saurya Karmacharya; Timothy J. Krupnik (Farming System)
South Asia's Eastern Indo-Gangetic Plain (EIGP) of India, Nepal, and Bangladesh is home to approximately 450 million people and predominantly rely on agriculture for livelihood. Agriculture is highly cereal-centric in EIGP. Increasing crop diversification within the EIGP region could improve agricultural sustainability, but knowledge of the spatiotemporal patterns of crop diversification and how it varies across EIGP countries is limited. In this study, we used historical sub-national crop data from India (1966–2022), Nepal (2000–2022), and Bangladesh (1971–2022) to measure crop diversification and compare it with the existing sub-district level scale. Crop diversification was measured using the Herfindahl-Hirschman Index (HHI). We found a noticeable increase in overall crop diversification in EIGP during this period but with spatiotemporal variations between the countries and seasons. Furthermore, while comparing sub-national patterns with existing sub-district patterns, we found opposing trends. Our data suggest that sub-national diversification patterns are an aggregate measure that may obscure the diversification pattern at the district, sub-strict, and even community level diversification. Measurements of sub-national crop diversification may appear to have moderate diversification overall, but this could result from some districts having high levels of diversification while others more oriented towards monocropping and a lack of diverse crop rotations. Our findings provide a new approach and a baseline of crop diversification in the EIGP for future research and interventions agricultural policy and development planners.